In vitro prion-like behaviour of TDP-43 in ALS - Smethurst, Phillip (Neurobiol Dis, 2016)
Amyotrophic lateral sclerosis (ALS) is the most common form of motor neuron disease (MND), and > 95% of familial and sporadic cases involve the deposition of insoluble aggregated, phosphorylated and cleaved TDP-43 protein. Accumulating clinical and biological evidence now indicates that ALS bears a number of similarities to the prion diseases, with TDP-43 acting as a misfolded ‘prion-like’ protein demonstrating similar underlying pathobiology. Here we systematically address the hypothesis that ALS is a prion-like disorder. First we demonstrate that TDP-43 demonstrates seeded polymerisation in vitro directly from both ALS brain and spinal cord. We next show that the seeding of TDP-43 results in the formation of characteristic insoluble, aggregated, and phosphorylated TDP-43 pathology that directly recapitulates the morphological diversity of TDP-43 inclusions detected in ALS patient CNS tissue. We next demonstrate that this reaction can be serially propagated to produce increasing amounts of phosphorylated TDP-43 pathology, and that aggregates can spread from cell to cell in an analogous fashion to that seen in the prion diseases. Finally, we reproduced our findings in a murine motor neuron-like cell line (NSC-34), where the seeding of TDP-43 induces the formation of TDP-43 oligomers and reduced cell viability. These findings may guide therapeutic strategies in this rapidly progressive and invariably fatal disease.